2020
DOI: 10.2147/nsa.s243017
|View full text |Cite
|
Sign up to set email alerts
|

<p>Nanoparticle Drug Delivery Systems for α-Mangostin</p>

Abstract: α-Mangostin, a xanthone derivative from the pericarp of Garcinia mangostana L., has numerous bioactivities and pharmacological properties. However, α-mangostin has low aqueous solubility and poor target selectivity in the human body. Recently, nanoparticle drug delivery systems have become an excellent technique to improve the physicochemical properties and effectiveness of drugs. Therefore, many efforts have been made to overcome the limitations of α-mangostin through nanoparticle formulations. Our review aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 104 publications
1
32
0
Order By: Relevance
“…The formulation of NPs affects their biopharmaceutical, pharmacokinetic, and pharmacodynamic aspects. In addition, polymeric NPs provide targeted delivery and significantly enhance AMG biodistribution to specific organs [ 105 ].…”
Section: Nanotechnology Of Amg In Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…The formulation of NPs affects their biopharmaceutical, pharmacokinetic, and pharmacodynamic aspects. In addition, polymeric NPs provide targeted delivery and significantly enhance AMG biodistribution to specific organs [ 105 ].…”
Section: Nanotechnology Of Amg In Breast Cancermentioning
confidence: 99%
“…Bonafe et al demonstrated that AMG loaded in CD44 Thioaptamer-tagged NPs reduces the number of BC cancer cells [ 7 ]. NPs that mediate passive or active target delivery are generally prepared with a high affinity for the target and low affinity for normal cells [ 105 ].…”
Section: Nanotechnology Of Amg In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Biocompatibility is one of the most important criteria in biomaterials selection. ChNPs can be administered orally and intravenously into host cells [ 21 ]. ChNPs are used as a drug delivery system targeted at cancer therapy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many drugs and bioactive substances have some inconveniences in use; therefore, nanoparticle delivery systems were developed to improve the bioavailability and effectiveness of these substances (Wathoni et al 2020). Nanostructured lipid carriers (NLC) are lipid nanoparticles composed of a solid lipid matrix incorporated with liquid lipid or oil (E Eleraky et al 2020).…”
Section: Introductionmentioning
confidence: 99%